A mixed interval type-2 fuzzy best-worst MACBETH approach to choose hub airport in developing countries: case of Iranian passenger airports - Pishdar, Mahsa; Ghasemzadeh, Fatemeh; Antuchevičienė, Jurgita (Transport, 2019)
Hub airports are the ones that model networks in which most journeys go via a few central points. Famous hub airports deliver positive social and environmental impact to the communities along with economic effects. This paper is about to investigate indicators related to hub performance excellence from various angles, considering leading hub airports performance while determining the priorities in order to help airports especially in developing countries to find the way of progress. A list of Key Performance Indicators (KPIs) is prepared from the literature, which is prioritized using Best-Worst Method (BWM). The weights of these criteria are specified via application of interval type-2 fuzzy BWM. Then using five most important criteria, MACBETH (Measuring Attractiveness by a Categorical Based Evaluation TecHnique) ranking approach is used to analyse 19 Iranian international airports and find the most appropriate one for being hub airport. The results show Kish airport with the International Civil Aviation Organization (ICAO) code “OIBK” is prior to other airports and can be chosen as the hub airport that means Iran airports holding company is suggested to focus more investments in this airport to gain fastest possible benefits of an international hub airport.